Designing with objects : object-oriented design patterns explained with stories from Harry Potter - Kak, Avinash C. (Hoboken, New Jersey : Wiley, 2015)
' All code examples in the book are available for download on a companion site with resources for readers and instructors. A refreshing alternative to the rather abstract and dry explanations of the object-oriented design patterns in much of the existing literature on the subject In 24 chapters, Designing with Objects explains well-known design patterns by relating them to stories from the Harry Potter series'--
'Designing with Objects is the only book that explains object-oriented design patterns through examples that are based on Harry Potter stories'--
Includes index.
Keywords: Rowling, J. K. -- Themes, motives; Rowling, J. K. -- Characters; Potter, Harry -- (Fictitious character).; Object-oriented programming (Computer science).